Soil investigation at Wet World Hot Spring Complex for future development using active multichannel analysis of surface waves - Khalil, Amin E.; Mohd Nawawi,; M. Hariri Arifin,; Abdullah, Fathi M.; J.S. Kayode,; Nuraddeen Usman,; Arisona, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Development of hot spring touristic projects receives more interest in Malaysia in recent years since the country has a high potential of hot springs that are vital to the economy. However, such developmental activities could produce negative impacts if not accompanied with adequate knowledge of the subsurface conditions. Active multichannel analysis of surface waves (MASW) was applied to determine the subsurface shear wave velocities and Vs30. The inverted shear waves velocity models have then presented in both vertical cross-sectional plots and depth slices maps. Depth slices were chosen at about 5, 18.5 m and 32 m depths. Model obtained showed that the soil is stiffer near the highway side and turns to be softer as we go away in the scrub direction. Vs30 is also estimated and mapped to show the quality of the soil. Inverted parameters showed that the soil at the site ranges from soft soil to stiff one. Also, the result obtained proposed that the surface occurrence of the hot spring might be a result of intersection of faulted segments, where hot spring is located near the intersection points. Furthermore, the model helped in proposing a suitable for complex extension. The proposed is chosen such that it minimize any possible effects on the geothermal resources at the site.